Indications and outcomes of enucleation versus formal pancreatectomy for pancreatic neuroendocrine tumors. Issue 3 (March 2021) - Heidsma, Charlotte M.; Tsilimigras, Diamantis I.; van Dieren, Susan; Rocha, Flavio; Abbott, Daniel E.; Fields, Ryan; Smith, Paula M.; Poultsides, George A.; Cho, Cliff; Dillhoff, Mary; Lopez-Aguiar, Alexandra G.; Kanji, Zaheer; et al.
Abstract: Background: Pancreatoduodenectomy (PD) or distal pancreatectomy (DP) are common procedures for patients with a pancreatic neuroendocrine tumor (pNET). Nevertheless, certain patients may benefit from a pancreas-preserving resection such as enucleation (EN). The aim of this study was to define the indications and differences in long-term outcomes among patients undergoing EN and PD/DP. Methods: Patients undergoing resection of a pNET between 1992 and 2016 were identified. Indications and outcomes were evaluated, and propensity score matching (PSM) analysis was performed to compare long-term outcomes between patients who underwent EN versus PD/DP. Results: Among 1034 patients, 143 (13.8%) underwent EN, 304 (29.4%) PD, and 587 (56.8%) DP. Indications for EN were small size (1.5 cm, IQR:1.0–1.9), functional tumors (58.0%) that were mainly insulinomas (51.7%). After PSM (n = 109 per group), incidence of postoperative pancreatic fistula (POPF) grade B/C was higher after EN (24.5%) compared with PD/DP (14.0%) (p = 0.049). Median recurrence-free survival (RFS) was comparable among patients who underwent EN (47 months, 95% CI:23–71) versus PD/DP (37 months, 95% CI: 33–47, p = 0.480). Conclusion: Comparable long-term outcomes were noted among patients who underwent EN versus PD/DP for pNET. The incidence of clinically significant POPF was higher after EN.